The problem states: Find dw/dt (a) using the appropriate chain rule and (b) by converting w to a function of t before differentiating.

w = xy x = s sin t, y = cos t

the solution in my solution manual goes like this:

a) using the chain rule they come up with: 2y cos t + x(-sin t) = 2y cos t - x sin t =

2(cos^2t - sin^2t) = 2 cos 2t

b) w = 2 sin t cos t = sin 2t, dw/dt = 2 cos 2t

I cannot follow this solution at all. I'm not certain how to even begin to solve it.
Could someone help me make sense of this by showing me how they go from one step to the other?

Solution Preview

w=xy, x=2sint, y=cost
Let me explain (a).
by the product rule of differentiation, (xy)'=xy'+yx'. Now x=2sint, then x'=2cost because (sint)'=cost is a basic derivative formula. y=cost, then y'=-sint is also a basic ...

Solution Summary

Partial Differentiation and the Chain rule are investigated.

... order partial derivatives to investigate the accuracy of 41 as an estimate of f(x,y) for values of x and y in these ranges? How would I use the chain rule to ...

... We can simplify the partial derivative (dP/dV)_S by dividing (4) and (6). The ordinary chain rule is valid, provided we keep the same variable constant. ...

... Incomplete solutions will receive partial credit ... 1 Given = +2 +3 a) Find the difference quotient +ℎ − ℎ b ... formula given below to find the derivative of the ...

... that in (5) we have used the chain rule ∂Ar ∂xs ... To summarize, we have the transformation rule. ... tensor because of the second order partial derivative on the ...

... this can be done using the chain rule as follows ... squared term by noticing that the derivative of cotangent ... 9. Find the partial fraction expansion: (not sure how ...

... fz are partial derivatives. 5) Prove that if f(r) and g(r) are any two scalar functions of r, then ⊗(fg) = f ⊗ g + g ⊗ f. Proof. By the chain rule, we ...

... planning in terms of operating partial networks, using ... The differentiation of firms into these stages rests ... the most vulnerable links in firms' value chains. ...

... functions xi and xj are independent, we have, by the chain rule, that. ... xk ∂xl Substituting Akl = −Alk and rearranging the partial derivatives, we obtain. ...

... the group composition law, es- sentially because the partial derivatives form matrix ... y β ∂ ∂ xµ → xµ one has, using the chain rule ∂xα ≡ ∂xα ...